Face stability of a tunnel excavated in saturated nonhomogeneous soils - Zou, Jin-feng; Qian, Ze-hang; Xiang, Xin-hai; Chen, Guang hui (Tunnelling and underground space technology, 2019)
Most subways excavated in nonhomogeneous and water-bearing soils but few existing analytical models focus on the combined effect of soil nonhomogeneity and pore water pressures. To address this issue, a three-dimensional (3D) rotational collapse mechanism is improved to investigate the effect of vertical variability of soil strength on the face stability of a circular tunnel excavated in saturated nonhomogeneous soils by means of the kinematical approach of limit analysis. The pore water pressure distribution obtained numerically is interpolated on the 3D improved collapse mechanism by a linear interpolation technology. The effectiveness of the developed model is verified by comparing the required face pressures with the existing solutions, the numerical simulations and the monitoring data of the Shenzhen urban rail transit line 9 project. The effects of nonhomogeneous friction angles and cohesion and water table elevation on the face stability are investigated.